Розвиток скотарства в контексті розвитку сільських територій - Шиян, Наталія Іванівна (Видавництво Харківського регіонального інституту державного управління Національної академії державного управління при Президентові України "Магістр", 2019)
Доведено необхідність розвитку скотарства в аграрних підприємствах. Саме розвиток галузі скотарства, супроводжуваний збільшенням чисельності працюючих в аграрній сфері, зростанням обсягів виробництва продукції галузі, збільшенням величини заробітної плати, яку отримують робітники підприємства, сприяє збільшенню надходжень до місцевих бюджетів у вигляді податку з фізичних осіб. Доведено, що поглиблення рівня спеціалізації підприємств на виробництво продукції тварин ництва і скотарства сприяє підвищенню заробітної плати і податку з фізичних осіб із розра хунку на 100 га сільськогосподарських угідь, що сприяє збільшенню доходів бюджету терито ріальних громад.

The article deals with the actual problem of Ukrainian rural territories’ development, their role in socio-economic life of the rural population. The emphasis is on the priority development of rural areas according to the directions of the state policy of Ukraine focusing on raising living standards of rural population, improving environment conditions, and so on. The importance of replenishing local budgets and budgets of association of territorial communities for the realization of their functions has been determined. The purpose of this study is to consider one of the signi cant replenishment sources of local budgets and budgets of the association of territorial communities - personal income tax. According to Article 63 Section III of the Budget Code of Ukraine, they receive 60% of this tax. Therefore, to increase revenues to the budget, there is a need to increase the tax base, including the income from individuals. Salaries at agricultural enterprises are one of the taxation bases of this tax. According to the Tax Code of Ukraine, the tax rate is 18%. The study was carried out using data from agricultural enterprises, reported according to the form 50 for agriculture in general in Ukraine, and per zones. Data for 2010 and 2016 were analyzed. In the course of the study, the amount of tax paid to the local budget and the budget of the united territorial community per 100 hectares of agricultural land was calculated. The calculations were carried out at enterprises with different levels of specialization in the production of the livestock sector, including cattle breeding. Having analyzed the wages of the workers in the livestock sector, including the cattle-breeding and the tax on individuals sent to the local budget and the budget of the territorial communities, the conclusion was made: deeper specialization of enterprises in the production of livestock and cattle breeding products contributes to the increase in wages and taxes from individuals per 100 hectares of agricultural land, which leads to the increase in the revenues to the local budget and the budget of the territorial communities. Development of the livestock sector, in particular, the cattle breeding sector, has a positive social impact on the development of rural areas.
Cattle breeding in the context of rural territorial development
Keywords: сільські території; заробітна плата; податки; бюджети територіальних громад; rural territories; wages; taxes; budgets of territorial communities